Squeezed flow of a nanofluid with Cattaneo–Christov heat and mass fluxes - Noor Muhammad (Results in Physics, 2017)
In this article mathematical model is developed for squeezing flow of viscous fluid with heat and mass fluxes using Cattaneo–Christov theory. Characteristics of flow are explored with thermal and solutal stratification phenomena. Disturbance in the fluid is induced by a linear stretching sheet which is characterized by lower plate. The System of arising partial differential equations are reduced to a system of ordinary differential equations by utilizing suitable transformations. The graphical behavior of various parameters on velocity, temperature, and concentration distributions are analyzed and discussed. It is noted that thermal and solutal relaxation parameters result in the reduction of temperature and concentration distribution respectively. Keywords: Viscous nanofluid, Cattaneo–Christov heat and mass fluxes, Unsteady stretching plate, Double stratification, OHAM solutions